First principle study on copper passivated armchair graphene nanoribbon for a supercapacitor electrode material - Paz, Kyle Alfred C. (Animo Repository, 2022)
Density functional theory was employed to calculate the electronic properties of three armchair graphene nanoribbon systems (AGNR). The first system is hydrogen-passivated (H-AGNR-H), the second is passivated on one side with copper (Cu-AGNR-H), and the third is passivated on both sides with copper (Cu-AGNR-Cu). The calculations were carried out using 1x20x1 k-points with kinetic cut-off energy of 70 Ry and 700 Ry for the wave function and the charge density, respectively. Based on the formation energies, all three systems are structurally stable when compared to other nanoribbon systems, with the H-AGNR-H (-0.8228 eV) being the most stable, while Cu–AGNR-H (-0.5429 eV) is more stable than Cu-AGNR-Cu (-0.2762 eV). The quantum capacitance and the total surface charge were computed to quantify the material’s properties as a supercapacitor. Cu-AGNR-Cu showed superior quantum capacitance and surface charge values, while Cu-AGNR-H showed vast improvements when compared to H-AGNR-H. With the greatest structural stability and optimal quantum capacitance and surface charge values, the Cu-AGNR-H system is the most viable material for electrodes among the three nanoribbon systems.